Evaluation of complement components C3 and C4 in serum of patient with neoplastic diseases - weheed Atwan, Zeenah; Jawad Al-Ali, Shereen; Abbas Mehdy, Mohamed (University of Thi-Qar Journal of Science, 2010)
The aim of this study is to evaluate the level of complement components C3 and C4 in serum of cancer patients to find which activation pathway of the complment system has the more effect in these cases . A total of 20 blood samples were collected from cancer patients , C3 and C4 complement components were measured by SRID plates . The results showed a significant elevation in C3 and C4 level in compartion with control group. C3 level was higher than C4 level which suggest that the activation of classical pathway in cancer patients .